Therapeutic Management of Paracetamol Toxicity in Dogs: A Study of Six Cases - Shah, Aditya I; Parmar, Jignesh J; Rao, Neha; Sadhu, Dashrath B; Hadiya , Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The analgesics and antipyretics such as paracetamol,  bruphen and aspirin are mostly used medication in  human being, paracetamol shows less side effects like  less gastric irritation and bleeding (Khan, 1995). Due to its  easy avaibility and non-narcotic nature people keep them  in houses and consume without any advice of experts,  whenever needed, and also use for their pets. Sometimes  the pets specially dogs and cats also ingest accidently these  medications. The reports of paracetamol toxicity especially in  dogs are meager. This paper presents toxicity of paracetamol  in dogs and its successful therapeutic management.
Keywords: avaibility; medications.; management.; especially; successful